Ethnophysical Analysis of Sigale-Gale Statue Performance as Physics Learning Resources - Wilujeng, Sri; Andari, Ruri; Irawan, Aprita; Sibarani, Vanni Intan Medika; Panjaitan, Maya Sari; Manurung, Nadila Anugraini Br; Panggabean, Deo Demonta (Universitas Pendidikan Mandalika, 2025)
Physics learning is often perceived as challenging by students due to the abundance of formulas and abstract theories, as well as the lack of contextual learning resources. One approach that can be implemented to enhance students' interest and understanding is integrating local wisdom into physics learning through ethnophysics. This study aims to identify physics concepts in the Sigale-Gale puppet performance in North Sumatra and to analyze how the ethnophysical approach can be utilized to create more contextual and meaningful learning experiences. This research serves as an initial study of North Sumatran cultural performances in the context of physics. The method used is qualitative, in the form of a literature review. The results indicate that the Sigale-Gale performance encompasses various physics concepts, such as sound waves produced by gondang musical instruments, and the principles of motion, levers, balance, and acceleration embedded in the puppet’s mechanism. By applying the ethnophysical approach, students can gain a more tangible understanding of physics while also helping to preserve local culture. These findings can serve as a foundation for developing lesson plans (RPP) based on local culture, making physics learning more enjoyable, interactive, and meaningful.